Celiac Disease and Gluten-Free Diet - Rodrigo, Luis (IntechOpen, 2023)
Celiac disease is an autoimmune disease that primarily affects the small intestine, causing chronic inflammation and sometimes villous atrophy. It is related to the ingestion of gluten products and affects genetically susceptible people. This book provides a comprehensive overview of celiac disease, presenting information on its diagnosis and management.